Doubling farmers’ income in Delhi state: An introspection - Kar, Amit; Kumar, Pramod; Prakash, P; Singh, D R; Dabas, J P; Gowda, Sathish; S, C; Deepak, Nayan; Pooniya, Vijay; Bana, R S (The Indian Journal of Agricultural Sciences, 2020)
The state of Delhi is fast growing in terms of urbanisation which is putting a lot of pressure on the agriculture sector of the state. The state is impacted due to fast declining area under agriculture and large urban population to meet the food requirement. In the past the policies were framed to enhance production but of late it is increase in income of the farmers that has become of prime importance. In this background the study was taken up to analyse the problems and prospects of agricultural sector of Delhi state and to suggest strategies for doubling the farmers’ income. Intensive primary survey and focus group discussions of 180 farm households were conducted for the study by using pre-tested questionnaire. A linear programming model was used for assessing the optimal crop enterprise combination. The study revealed that the reorientation of crop enterprise towards vegetables, fruits and flowers in combination with allied enterprises like apiary and dairy would enhance the farmers income up to 53% to 198% under various categories of farmers. Further, the availability of loans up to 40% of existing capital would augment the farm income to the tune of 110% to 251%.The study suggest that agriculture be declared as an enterprise which will help farmers to get benefit of government schemes. There exists huge scope for post-harvest processing and value addition of vegetables, wheat, rice, etc. The farmers need to be organised like FPO, SHGs, etc., so that their bargaining power is increased and farmers are able to realise better price for their farm products.